Research Trends on Leadership in Indonesian Schools: Bibliometric Analysis (2008-2024) - Brilliant Dwi Izzulhaq; Gunawan, Resky Nuralisa; Zafrullah, Zafrullah; Ayuni, Rizki Tika; Ramadhani, Atika Miftah; Fitria, Rani Laylatul (Penerbit Hellow Pustaka, 2024)
This research aims to analyze research trends regarding leadership in Indonesian schools on the Scopus database. Using the PRISMA method, the author analyzed documents to obtain 111 documents which were analyzed using the R Program and Vosviewer. From the results of the analysis that has been carried out, it can be concluded that research on Leadership in Indonesian schools started from 2008 to 2024, with an 8-fold increase in the last six years. Malang State University ranks first with the highest contribution in research on leadership in Indonesian schools, producing 45 publications or 40.54% of the total. Cakrawala Pendidikan, published by Yogyakarta State University, holds the top position with an h-index of 3, signifying its significant impact in the field of educational research. Maulana Amirul Adha from Jakarta State University holds the top position with an h-index of 4, reflecting his significant impact in educational research. The highest citation obtained by the article (Wiyono, 2018) with a total of 47 citations. The results obtained are 20 keywords with five groups, with the words “School Principal,” “Teacher,” and “Servant Leadership” stand out as areas worthy of further research regarding the topic of leadership in Indonesian schools.